Nanodispersions Interactions, Stability, and Dynamics - Ruckenstein, Eli; Manciu, Marian (Springer New York : Imprint: Springer, 2010)
This book collects a number of papers on nanodispersion interactions, dynamics and stability by Eli Ruckenstein and his research group at The State University of New York at Buffalo. Each paper provides insight into nanotechnology and fills the growing need for a basic understanding of nanoparticle interactions and their role in the thermodynamic or kinetic stability of nanodispersions. They should appeal to those applying nanotechnology to chemistry, biophysics, materials science, colloid science, polymer science, and chemical engineering.